(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Tuberculosis (TB) is a chronic granulomatous disease caused by Mycobacterium tuberculosis. Mycobacterium avium complex (MAC) infections are not only more common but also rapidly progress in these patients. First-line drugs are superior in efficacy to second-line drugs. Most patients can be treated successfully with these drugs.